2018
DOI: 10.1074/jbc.m117.812693
|View full text |Cite
|
Sign up to set email alerts
|

Communication between N terminus and loop2 tunes Orai activation

Abstract: Ca2+ release-activated Ca2+ (CRAC) channels constitute the major Ca2+ entry pathway into the cell. They are fully reconstituted via intermembrane coupling of the Ca2+-selective Orai channel and the Ca2+-sensing protein STIM1. In addition to the Orai C terminus, the main coupling site for STIM1, the Orai N terminus is indispensable for Orai channel gating. Although the extended transmembrane Orai N-terminal region (Orai1 amino acids 73–91; Orai3 amino acids 48–65) is fully conserved in the Orai1 and Orai3 isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(113 citation statements)
references
References 72 publications
2
107
1
3
Order By: Relevance
“…This conclusion is consistent with other recent studies that have examined the contribution of the membrane-proximal N terminus for Orai1 gating (16,31). We do not yet know how the Orai1 N terminus contributes to channel function, but possible explanations could include an interaction with another part of Orai1 in the open state (40) or a role in ion permeation (41).…”
Section: Discussionsupporting
confidence: 92%
“…This conclusion is consistent with other recent studies that have examined the contribution of the membrane-proximal N terminus for Orai1 gating (16,31). We do not yet know how the Orai1 N terminus contributes to channel function, but possible explanations could include an interaction with another part of Orai1 in the open state (40) or a role in ion permeation (41).…”
Section: Discussionsupporting
confidence: 92%
“…1C). Recent evidence indicates that the 2-3 loop mediates important communication with the M1-ext helix (43). Although the C-terminal M4-ext is the primary site for STIM1 binding to gate the channel, we would speculate that the entire cytosolic domain (M1-ext, 2-3 loop, and M4-ext) exists as a conformationally coupled entity, the alteration of which affects both STIM1 binding and gating of the channel.…”
Section: Function Of Orai1 Dimersmentioning
confidence: 91%
“…observed that the loss of current in Orai1 N‐terminal truncation mutants (∆1–78) can be partially restored by replacing the native Orai1 TM2–3 loop with that of Orai3 (Fahrner et al . ). They postulated that the inhibition of current seen in the N‐terminally truncated Orai1 channels occurs because of an interaction between the truncated Orai1 N‐terminus and the TM2–3 loop (Fahrner et al .…”
Section: How Does Stim1 Binding Activate Orai1?mentioning
confidence: 97%
“…They postulated that the inhibition of current seen in the N‐terminally truncated Orai1 channels occurs because of an interaction between the truncated Orai1 N‐terminus and the TM2–3 loop (Fahrner et al . ). Consistent with this idea, cysteine cross‐linking between the N‐terminus and the TM2–3 loop inhibited currents in STIM1‐gated and P245L constitutively active mutant channels (Fahrner et al .…”
Section: How Does Stim1 Binding Activate Orai1?mentioning
confidence: 97%
See 1 more Smart Citation